Numerical characterization of the magnetic field in electric vehicles equipped with a WPT system. Issue 2 (14th June 2017) - Campi, Tommaso; Cruciani, Silvano; De Santis, Valerio; Maradei, Francesca; Feliziani, Mauro
Abstract : This paper deals with the numerical evaluation of the magnetic field emitted by a wireless power system (WPT) in an electric vehicle (EV). The numerical investigation is carried out using a finite element method (FEM) code with a transition boundary condition (TBC) to model conductive materials. First, the TBC has been validated by comparison with the exact solution in simple computational domains with conductive panels at frequencies used in WPT automotive. Then, the FEM with TBC has been used to predict the field in an electric car assuming the chassis made by three different materials: steel, aluminum, and fiber composite. The magnetic field source is given by a WPT system with 7.7 kW power level operating at frequencies of 85 or 150 kHz. The calculated magnetic field has been compared with the International Commission on Non-Ionizing Radiation Protection (ICNIRP) reference level demonstrating compliance for an EV with metallic (steel or aluminum) chassis. On the contrary, a fiber composite chassis is much more penetrable by magnetic fields and the reference level is exceeded.